Economic Recession In Nigeria: An Important Risk Factor For Suicide - Asogwa, Emmanuel U.; Onyezere, John. O. (Archives of Business Research, 2018)
There was a general belief and assumption that Nigerians so much love life that none of its citizens can ever think of taking his own life. This might have been responsible for the World Values Survey Report in 2003, which ranked Nigerians among the happiest people in the world, and the 6th happiest people in Africa, and 95th in the world by the United Nations (UN) in spite of the glaring challenges confronting them. However, these good stories may have been faulted and the general belief and assumption dispersed by the worrisome high rates of suicide in Nigeria few months into economic recession, which started in the first quarter of 2016. This development is strange to Nigerians, and in view of this, there are grounds to consider an association between economic recession and increased suicide rates. This study, therefore, intends to establish that economic recession is an important risk factor for suicide, and recommend measures to prevent recession-induced suicide.